A facile strategy for observation of helical carbon nanofiber fillers in polymer matrix under different stresses. (January 2021) - Zhang, Wei; Liu, Suyi; Gong, Yong; Zhang, Yiguo; Chen, Jian; Fu, Qingshan
Abstract: Dispersion of fillers in polymer substrates is crucial to the mechanical performance of filler/polymer composites. Kinds of methods have been utilized to assess the dispersion of fillers in polymer. However, it still keeps difficulties in observing the dispersion of fillers and plausible structure changes of fillers when the filler/polymer hybrids are loaded with variable stresses. Here, an effective tool is designed to load and hold different stresses in filler/polymer hybrids, and combined with embedding process the loaded hybrids can be fixed. In this work, helical carbon nanofibers (HCNFs) are fabricated and added in natural rubber (NR). The HCNFs/NR hybrids are loaded with different stress by the aforementioned tool and then are embedded in solidified adhesion. Flat surfaces on the indurated samples are achieved using microtome cryostat and observed in a scanning probe microscope (SPM). Experimental results show that HCNFs and the rubber matrix do not perform synergistic deformation under the different external forces; when under lower stress the pitch of HCNFs exhibits less elongation than the HCNFs/NR hybrids. While the tensile force increases to a certain extent, HCNFs will be aligned in the direction of the stress direction, leading to the change of dispersion. The mechanically interlock between HNCFs and NR is also demonstrated. Highlights: A facile route is designed for load and hold different stresses in HCNFs/NR hybrids. Dispersion of HCNFs under different stresses can be observed conveniently by SPM. The changes of HCNFs in hybrids under different stresses are also determined clearly. HCNFs and NR do not exhibit synergistic deformation under external forces.